2020
DOI: 10.1016/j.compbiomed.2020.104025
|View full text |Cite
|
Sign up to set email alerts
|

Micropolar pulsatile blood flow conveying nanoparticles in a stenotic tapered artery: NON-Newtonian pharmacodynamic simulation

Abstract: Two-dimensional rheological laminar hemodynamics through a diseased tapered artery with a mild stenosis present is simulated theoretically and computationally. The effect of different metallic nanoparticles homogeneously suspended in the blood is considered, motivated by drug delivery (pharmacology) applications. The Eringen micropolar model has been deployed for hemorheological characteristics in the whole arterial region. The conservation equations for mass, linear momentum, angular momentum (micro-rotation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 61 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Computational fluid dynamics studies of nano-drug delivery have featured a wide spectrum of numerical techniques, nanoscale models and rheological material models. Vasu et al [4] reported the first finite difference computational results for nanoparticle doped-micropolar blood flow through a diseased tapered vessel with the Buongiorno model. They computed the impact of vessel taper angle, Prandtl number, Womersley parameter, Brownian motion and thermophoresis on velocity, temperature, micro-rotational (Eringen angular) velocity, nanoparticle concentration, wall shear stress, volumetric flow rate and hemodynamic impedance.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics studies of nano-drug delivery have featured a wide spectrum of numerical techniques, nanoscale models and rheological material models. Vasu et al [4] reported the first finite difference computational results for nanoparticle doped-micropolar blood flow through a diseased tapered vessel with the Buongiorno model. They computed the impact of vessel taper angle, Prandtl number, Womersley parameter, Brownian motion and thermophoresis on velocity, temperature, micro-rotational (Eringen angular) velocity, nanoparticle concentration, wall shear stress, volumetric flow rate and hemodynamic impedance.…”
Section: Introductionmentioning
confidence: 99%
“…The Keller-box implicit finite difference method was used to solve non-linear system of equations. Vasu et al 88 considered two-dimensional non-Newtonian blood flow through a stenosed coronary artery with a suspension of nanoparticles. For the convection of nanoparticles in the blood, Buongiorno's model again was considered.…”
Section: Single-phase Approachesmentioning
confidence: 99%
“…Investigational and numerical inspection of flow characteristics with energy transfer in a channel for pulsating flow was done by Zhang et al 35 . Vasu et al 36 made a novel model of pulsating micropolar flow of blood carrying nanoparticles in a stenosed narrowing blood vessel for a drug delivery application of non-Newtonian pharmacodynamic simulation. An incompressible non-Newtonian pulsating fluid flow via penetrable medium with an episode of an inclined uniform magnetic field is analytically studied by Bitla and Iyengar 37 .…”
Section: Introductionmentioning
confidence: 99%